Residues of the Cork Industry as Carriers for the Production of Legume Inoculants - Ferreira,Eugénio Mendes (2005)
Growth and survival of two rhizobial strains, Rhizobium leguminosarum bv. trifolii, and Mesorhizobium ciceri, were used to evaluate residues from the cork industry as potential carriers for production of rhizobial inoculants. A peat-based carrier was used as a control. 41 days after inoculation, the number of viable bacteria was high, about 10(9) bacteria g-1 for all carriers. Rhizobial survival during storage (450 days) remained stable, between 10(8) and 10(9). The cork residues based carriers showed good handling properties and water holding capacities, they were non-toxic and had a nearly neutral pH. All these factors indicate that the use of these carriers is viable for the production of rhizobial inoculants.